2016
DOI: 10.1039/c6ra21898a
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and cytotoxicity of polyketides isolated from the mushroom Xerula sp. BCC56836

Abstract: Thirteen new polyketides (1, 3, 5–12, and 14–16) together with nine known compounds were isolated from the mushroom Xerula sp. BCC56836.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…One is scalusamide A, an antifungal agent and its derivatives (B,C) isolated from Xerula sp. BCC56836 [ 113 ].…”
Section: Bioactivities and Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is scalusamide A, an antifungal agent and its derivatives (B,C) isolated from Xerula sp. BCC56836 [ 113 ].…”
Section: Bioactivities and Mode Of Actionmentioning
confidence: 99%
“…Sadorn et al [ 113 ] identified 12 ( Figure 7 ) different compounds from a Xerula sp. (strain BCC56836) in Thailand.…”
Section: Bioactivities and Mode Of Actionmentioning
confidence: 99%
“…The culture and chemical examination of Xerula sp. BCC56836 led to the isolation of (−)-oudemansin X (50) that showed significant activity with IC 50 of 1.19 µM against P. falciparum K1, while (−)-oudemansin A (51) was found moderately active with IC 50 value of 9.23 µM (Sadorn et al, 2016).…”
Section: Tablementioning
confidence: 99%
“…Along with new compounds, known spirocyclic azaphilon mycotoxin H1 ( 218 ) [ 78 , 204 ] was obtained when studying a mangrove fungus of the Cladosporium genus [ 121 ]. Similar compounds, new polyketide xerucitrinin A ( 219 ), xerucitriniс acid A ( 220 ) [ 205 ], and penicitrinins A ( 221 ) and F ( 222 ) [ 206 ], were obtained from a fungus of marine origin [ 108 ].…”
Section: Polyketides Xanthonoids and Related Compoundsmentioning
confidence: 99%
“…mangrove fungus of the Cladosporium genus[121]. Similar compounds, new polyketide xerucitrinin A (219), xerucitriniс acid A (220)[205], and penicitrinins A (221) and F (222)[206], were obtained from a fungus of marine origin[108].…”
mentioning
confidence: 93%